2015
DOI: 10.1002/mbo3.286
|View full text |Cite
|
Sign up to set email alerts
|

Loss of membrane‐bound lytic transglycosylases increases outer membrane permeability and β‐lactam sensitivity in Pseudomonas aeruginosa

Abstract: The opportunistic pathogen Pseudomonas aeruginosa is a leading cause of nosocomial infections. Its relatively impermeable outer membrane (OM) limits antibiotic entry, and a chromosomally encoded AmpC β‐lactamase inactivates β‐lactam antibiotics. AmpC expression is linked to peptidoglycan (PG) recycling, and soluble (sLT) or membrane‐bound (mLT) lytic transglycosylases are responsible for generating the anhydromuropeptides that induce AmpC expression. Thus, inhibition of LT activity could reduce AmpC‐mediated β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 81 publications
(246 reference statements)
3
99
1
Order By: Relevance
“…However, the accumulation of multiple mutations -each of which confers small increases in resistance -can lead to high-level resistance in a stepwise manner [2,[45][46][47][48]. While most studies focus on single mutations that confer high-level resistance, recent work from our laboratory [46,47] and others [44,49], confirm that high-level resistance is achievable by the accumulation of multiple mutations that alone confer low level resistance. This phenomenon has been referred to as 'creeping baselines' [48]; however, the frequency of such a phenomenon is difficult to assess in clinical isolates because creeping baselines are likely to be missed by most clinical microbiology procedures that focus on defined break points [27].…”
Section: Acquired Resistancementioning
confidence: 87%
See 3 more Smart Citations
“…However, the accumulation of multiple mutations -each of which confers small increases in resistance -can lead to high-level resistance in a stepwise manner [2,[45][46][47][48]. While most studies focus on single mutations that confer high-level resistance, recent work from our laboratory [46,47] and others [44,49], confirm that high-level resistance is achievable by the accumulation of multiple mutations that alone confer low level resistance. This phenomenon has been referred to as 'creeping baselines' [48]; however, the frequency of such a phenomenon is difficult to assess in clinical isolates because creeping baselines are likely to be missed by most clinical microbiology procedures that focus on defined break points [27].…”
Section: Acquired Resistancementioning
confidence: 87%
“…Studies in E. coli showed that loss of LT activity prevented AmpC induction; however, a recent study from our laboratory showed that P. aeruginosa strains lacking up to five of the ten known LTs Pseudomonas aeruginosa: targeting cell-wall metabolism for new antibacterial discovery & development Review continued to exhibit robust induction [46]. That study also unexpectedly revealed that the membrane-bound LTs (mLTs) were required for maintaining the structural integrity of the OM in P. aeruginosa.…”
Section: Lytic Transglycosylasesmentioning
confidence: 89%
See 2 more Smart Citations
“…In P. aeruginosa, the loss of Slt (PA3020) and MltF (PA3764) is associated with a decrease in b-lactam resistance [98]. However, the loss of SltB1 (PA4001) and MltB1 (PA4444) led to an AmpC-independent increase in resistance to b-lactams, piperacillin and cefotaxime [98,213]. The loss of the other P. aeruginosa LTs' MltA (PA1222), MltD (PA1812), MltF2 (PA2865), SltG (PA1171) and SltH (PA3992) did not change the resistance profile [98] ( Table 3).…”
Section: Cell-wall Recycling and Antibiotic Resistancementioning
confidence: 99%